Additional opportunities of remote pedagogical technologies in vocational education of foreign students - B. C. Meskhi; L. E. Pustovaya; E. M. Bayan; О. В. Sharygina (Moscow Polytechnic University, 2022)
Remote learning in vocational education of foreign students is demand of educationalservices in a globalized information environment. The article is devoted to the problems of improving the quality of foreign student's vocational education. The paper provides the choice of additional educational technology training, in particular distance learning, based on the person-focused approach. As an example the authors introduce the educational-and-methodological complex of courses "Methods and devices for environment control.Environmental monitoring" for students and masters in Master degree program «Theenvironment protection». This complex includes information, informative, control section and activities. Finally, it is emphasized that it is necessary to develop new teaching sections and learning resources in English for foreign students of distance learning to create e-books, manuals, information support, to develop new methods and forms of student's education and teachers-tutors training.